Experimental study on the effects of width and self-extinguishing on the upward flame spread for linen fabric - Jinju Zhou; Guoqing Zhu; Yunji Gao; Shuai Gao; Guoqiang Chai (Case Studies in Thermal Engineering, 2019)
Linen fabric has been widely applied to interior decoration, medical and health care, industrial fabrics and oil painting exhibitions due to its advantages of good hygroscopicity, strong air permeability, excellent health care functions. In this paper, a series of comparative experiments were performed to study the effects of sample width on upward flame spreading using linen fabric with various widths ranging from 4 to 8 cm and length of 1.6 m. The major conclusions are summarized as follows: when sample width is 4 cm or 5 cm, the upward spreading process can be divided into three typical stages: two-sided flame accelerated spread, one-sided flame self-extinguishing and one-sided flame stable spread. Whereas for samples with a width larger than 5 cm, the upward flame spreading only exhibits the two-sided flame accelerated spread stage. Moreover, the maximum pyrolysis height, steady pyrolysis height, maximum spread rate and steady spread rate increase with sample width. The relationship between maximum spread rate and sample width can be described by a power-law function. Furthermore, after the one-sided flame self-extinguishing occurs, the pyrolysis height and spread rate decrease dramatically, which can be explained using energy conservation. The ratio of pyrolysis length before and after the self-extinguishing is about 2.0, and the corresponding ratio of spread rate is also around 2.0. Keywords: One-sided self-extinguishing, Sample width, Upward flame spread, Linen fabric